Real Problem Solving as a Teaching Strategy for Physics Education: Case Study (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2021)
The project presents the application of the stages proposed by Poyla for solving problems in mathematics, which have been adapted in mechanical physic. Critical reading strategies have also been applied resulting in reading physical problems comprehensively. Objectives: To incorporate real problem solving as a teaching strategy in two mechanical physics courses (one experimental and another traditional), in order to characterize the group that applies the problem-solving strategy. To validate the problem-solving strategy in mechanical physics. Methods: Mixed research including analysis and contrast of results obtained from two control groups: one experimental (24 university students of Mechanical Physics) and another traditional (16 university students of Mechanical Physics). The control group approaches the study of the subjects in a traditional way where the problems proposed are solved intuitively and somehow mechanically. The experimental group solves the proposed problems by applying each of the stages of the proposed sequence. The experimental group solves the proposed problems by applying each of the stages of the proposed sequence. This study differs from previous studies in that most are related to problem-solving in mathematics and in this case, we focus on physics with the value of involving elements related to critical reading, which gives a more realistic look of the Physical phenomenon studied from the interpretation of its occurrence and how it impacts the environment, which favors its theoretical understanding and gives meaning to its mathematical modeling.